Citrate‐Citric Acid RNA Isolation (CiAR) for Fast, Low‐Cost, and Reliable RNA Extraction from Multiple Plant Species and Tissues. Issue 12 (7th December 2021) - Oñate‐Sánchez, Luis; Verdonk, Julian C.
Abstract: RNA isolation is routinely carried out in many laboratories for different downstream applications. Although protocols for this can vary between labs depending on the specific plant species and tissues under study and the preferences of their researchers, these protocols usually include the use of volatile organic and toxic chemicals. As an alternative, several companies offer less hazardous RNA extraction kits, but these kits significantly increase the cost per sample and are thus not affordable for every lab, especially when a large number of samples is to be processed. We have previously described a fast and efficient method for RNA isolation from plant vegetative tissues that requires only two home‐made, simple, inexpensive, and nontoxic buffers. Both buffers have low concentrations of citric acid and its sodium salt. The first buffer also contains a detergent to help with nucleic acid solubilization while keeping RNases inactive. The second buffer has sodium chloride at high molarity to separate protein from nucleic acids. RNA is precipitated, and contaminating DNA can then be optionally removed. Here, we describe and expand on this approach, which we call the citrate–citric acid RNA isolation, or CiAR, method. We provide a detailed description of the protocol, describe a modification to make it compatible with non‐vegetative tissues, and compile and extend the number of species and tissues to which it can be applied. © 2021 Wiley Periodicals LLC.